Process-Spray Functional Particles Produced in Spray Processes - Fritsching, Udo (Springer International Publishing : Imprint: Springer, 2016)
This book describes the latest research on producing functional particles using spray processes. The authors detail micro level elementary processes and phase boundaries, process analysis scaling and modeling, and macro level process functions and particle properties. They include numerical simulations and particulars of experiments for deriving process conditions for particle production.